The Impact of Sino-american Relations on the Semiconductor Industry : An Exploratory Study Using Game Theorectical Analysis - Wan, Li Lian (2011)
The accession to WTO by China has opened trade for the communist country and marks its emergence into a free market world. This also changes the way China interacts with the world’s biggest economy, the United States of America. In the past decade, the relationship has undergone a lot of rapid changes. This is primarily due to the changes in trade policies as China complies with the WTO framework. As trade expands between the two countries, so does the friction. One of the biggest disputes is the trade deficit the U.S. is currently having and China with its massive trade surplus has been blamed for causing this trade imbalance. The culprit, as claimed by the U.S., is the currency manipulation by the Chinese to gain competitive advantage.The People’s Republic has been actively trying to get more high-tech companies to relocate to its shores to boost its competency in the semiconductor arena. Since the U.S. is the leader in this technology segment thus many of the companies that China is trying to attract are American-owned. With such a serious accusation coming from its government, corporations are wary of moving its operations there. To make matters worse, intellectual property theft is also rampant in China with such lax enforcement attitude by its local authorities. This is also another deterrent for the high-tech companies to set up its newest and latest manufacturing for fear of the Chinese copying it blatantly. The Sino-American relations are also plagued with the Taiwan issue. As a thriving democracy, the U.S. has pledge to aid the Taiwanese in the event China uses force to reclaim the island nation. Taiwan’s position in wafer fabrication adds to the attractiveness of Taiwan returning to the mainland. This paper attempts to provide an overview of the frictions within the Sino-U.S. relations using a game theoretic approach. .